Methylation of class II transactivator gene promoter IV is not associated with susceptibility to Multiple Sclerosis - Ramagopalan, S; Dyment, D; Morrison, K; Herrera, B; Deluca, G; Lincoln, MR; Orton, S; Handunnetthi, L; Chao, M; Sadovnick, A; Ebers, G (BioMed Central, 2008)
Background: Multiple sclerosis (MS) is a complex trait in which alleles at or near the class II loci HLA-DRB1 and HLA-DQB1 contribute significantly to genetic risk. The MHC class II transactivator (MHC2TA) is the master controller of expression of class II genes, and methylation of the promoter of this gene has been previously been shown to alter its function. In this study we sought to assess whether or not methylation of the MHC2TA promoter pIV could contribute to MS disease aetiology. Methods: In DNA from peripheral blood mononuclear cells from a sample of 50 monozygotic disease discordant MS twins the MHC2TA promoter IV was sequenced and analysed by methylation specific PCR. Results: No methylation or sequence variation of the MHC2TA promoter pIV was found. Conclusion: The results of this study cannot support the notion that methylation of the pIV promoter of MHC2TA contributes to MS disease risk, although tissue and timing specific epigenetic modifications cannot be ruled out.